2019
DOI: 10.1039/c8fo01089g
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity potential of rare sugard-psicose by regulating lipid metabolism in rats

Abstract: Dietary supplementation of d-psicose could slow down fat accumulation in rats by regulating lipid metabolism related genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…The LDL receptor is regulated through sterol regulatory elementbinding protein 2 (SREBP-2), which has an important role in hepatic cholesterol homeostasis (Hua et al, 1993). SREBP-2 is down-regulated by AMP-activated protein kinase α (AMPKα) (Wang et al, 2018), and a recent study found enhancement of AMPKα expression in D-allulosefed rats (Chen et al, 2019). These findings suggest the possibility that D-allulose might down-regulate the LDL receptor by suppression of SREBP-2 through enhancement of AMPKα expression.…”
Section: Discussionmentioning
confidence: 99%
“…The LDL receptor is regulated through sterol regulatory elementbinding protein 2 (SREBP-2), which has an important role in hepatic cholesterol homeostasis (Hua et al, 1993). SREBP-2 is down-regulated by AMP-activated protein kinase α (AMPKα) (Wang et al, 2018), and a recent study found enhancement of AMPKα expression in D-allulosefed rats (Chen et al, 2019). These findings suggest the possibility that D-allulose might down-regulate the LDL receptor by suppression of SREBP-2 through enhancement of AMPKα expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in an attempt to produce functional foods aimed at low calorie and less sugar intake for T2D, D-psicose, a rare monosaccharide also known as D-allulose, is considered as a substitute for sugar with proven antihyperglycemic, antihyperlipidemic, and anti-inflammatory effects [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a genetic and health problem, as well as a social problem that seriously threatens human health. According to data from the World Health Organization (WHO) in 2016, 25% of adults worldwide were overweight [1,2]. Overweight and obesity can cause complications such as type 2 diabetes, high blood pressure, cancer, and non-alcoholic fatty liver disease (NAFLD) [3,4].…”
Section: Introductionmentioning
confidence: 99%